An integrated strategy for monitoring cetaceans in data-poor regions. (August 2022) - Liu, Mingming; Lin, Mingli; Dong, Lijun; Caruso, Francesco; Li, Songhai
Abstract: A fundamental issue in cetacean conservation is determining the occurrence, distribution, and habitat use of target species. However, these baselines are extremely deficient in many poorly investigated regions, making it challenging to inform conservation management initiatives. In this case study, we employed three complementary approaches to generate conservation baselines on a "Vulnerable" near-shore delphinid species, the Indo-Pacific humpback dolphin, Sousa chinensis, in the waters southwest of Hainan (SW Hainan), China. First, in late 2013, we conducted large-scale local ecological knowledge (LEK) surveys with 510 Hainanese fishers. Our LEK findings revealed that SW Hainan was a previously underreported area with numerous fishermen encounters of humpback dolphins dating back to the 1970s. Second, from 2014 to 2019, we conducted monthly boat-based visual surveys in SW Hainan. Our sighting data verified the reliability of previous LEK findings and further confirmed the year-round occurrence and species dominance of humpback dolphins in SW Hainan. Third, we applied a supplementary approach (stationary passive acoustic monitoring, PAM) to monitor dolphin biosonar activities in the region. Our 10-site PAM dataset from February 2018 to June 2019 indicated spatiotemporal variations in dolphin click detections. To conclude, our findings, derived from multiple approaches, provide a scientific basis for cetacean conservation management and marine spatial planning on a regional scale. More generally, this study offers an integrated monitoring strategy consisting of three step-by-step approaches, which can help conservationists, especially those who work in data-deficient waters, obtain critical baseline data on cetaceans in an efficient, timely, and reliable way. Highlights: Many methods can be applied to provide conservation-valuable insights into cetacean ecology, while each has its own pros and cons. Three approaches were integrated into a step-by-step monitoring strategy for cetacean conservation research in data-poor regions. This integrated strategy can offer a comprehensive understanding of cetacean occurrence, distribution, and habitat use patterns.